2017
DOI: 10.15548/jt.v24i2.271
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Problem Based Learning on EFL Students’ Critical Thinking Skill and Learning Outcome

Abstract: This research aims to examine the effect of Problem Based Learning (PBL) model to students’ critical thinking skill and learning outcome. It was conducted on the 11th graders of social science program at SMAN 6 Malang. The research material was the problems of demography. Research method was quasi experiment with non equivalent control group design. The data analysis used t-test technique. The research result showed that PBL learning model affected students’ critical thinking skill and learning outcome in SMAN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 8 publications
1
14
0
3
Order By: Relevance
“…Another excellence of PBL model is the possibility to develop a critical thinking skill (Akınoğlu & Tandoğan, 2007;Allison & Pan, 2011) through a scientific method (Kronberg & Griffin, 2000). During the problem solving process, students are able to refine their critical thinking skills (Bashith & Amin, 2017;Mundilarto & Ismoyo, 2017;Pusparini, Feronika & Bahriah, 2018;Ramadhani, Huda & Umam, 2019). Students are able to analyze and synthesize every single problem they face (Nasution et al 2016), so that several problem solvings can be obtained rather than only one problem.…”
Section: Introductionmentioning
confidence: 99%
“…Another excellence of PBL model is the possibility to develop a critical thinking skill (Akınoğlu & Tandoğan, 2007;Allison & Pan, 2011) through a scientific method (Kronberg & Griffin, 2000). During the problem solving process, students are able to refine their critical thinking skills (Bashith & Amin, 2017;Mundilarto & Ismoyo, 2017;Pusparini, Feronika & Bahriah, 2018;Ramadhani, Huda & Umam, 2019). Students are able to analyze and synthesize every single problem they face (Nasution et al 2016), so that several problem solvings can be obtained rather than only one problem.…”
Section: Introductionmentioning
confidence: 99%
“…Wirda, Haji & Khaldun (2015) also stated that student KPS in the material of optical equipment also increased with the average from 5.56 to 13.40 with an increasement in N-Gain of 0.63 by applying PBL model. From those previous studies, Bashith & Saiful (2017) suggest that the PBL should be an alternative teaching model which can be applied to enhance student critical thinking skill. Thus, in this study it is proven that the use of the PBL model can rise the students' KPS average by 1.25 or 3.47%.…”
Section: The Effect Of Mind Mapping Model On Student Kpsmentioning
confidence: 99%
“…In a class that implements problem-based learning, rather than directly being given learning materials, students are given authentic problems as their starting point to learn, which then will be discussed in groups, encouraging them to creatively and critically collect information and data to solve problems (Anazifa & Djukri, 2017;Bashith & Amin, 2017). For Lin (2015), the problem is not only the starting point; it is the centerpiece of the learning process.…”
Section: Characteristics Of Problem-based Learningmentioning
confidence: 99%
“…Nevertheless, divided arguments regarding problem-based learning are found. Some studies found the strengths of problem-based learning for enhancing students' 21 st -century skills (Anazifa & Djukri, 2017;Bashith & Amin, 2017;Duff, 2008;Ghufron & Ermawati, 2018;Hadi & Izzah, 2018;Iswandari et al, 2017;Lapuz & Fulgencio, 2020;Keong & Mohammed, 2015;Munawaroh, 2020;Yuberti et al, 2019). On the other hand, some studies found the complexity and challenges in implementing problem-based learning (Blundell & Berardi, 2016;Ceker & Ozdamli, 2016;Ghufron & Ermawati, 2018;Iswandari et al, 2017;Kassem, 2018;Miner-Romanoff, Rae, & Zakrzewki, 2019).…”
Section: Introductionmentioning
confidence: 99%